2011
DOI: 10.1177/1468017310386697
|View full text |Cite
|
Sign up to set email alerts
|

Still doing what we do: Defining social work in the 21st century

Abstract: Members of the Aotearoa New Zealand Association of Social Workers (ANZASW) were asked to provide their definition of social work. Over 300 responses were analysed thematically in order to determine if practitioner views corresponded to recent shifts in social work education and theory which emphasized the importance of social change, strengths based perspectives and the importance of local and indigenous contexts.Findings: The findings demonstrate that while there was some recognition of social change and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
(37 reference statements)
0
34
0
2
Order By: Relevance
“…Its spread and development have been accompanied by a drive to attain professional status and a coherent international identity through the work of a number of international organisations concerned with social work practice and education, such as the International Federation of Social Workers (IFSW) and the International Association of Schools of Social Work (IASSW). An obvious manifestation of this is the continuing drive to develop a single global definition of what social work actually is [14][15][16]. The global nature of the profession is reflected in the large number of international professional and academic social work publications and, in Europe, the imperatives of various EU directives and initiatives like the Bologna Declaration have motivated social work educators and registering authorities International Journal of Population Research 3 to move towards a closer alignment of practice standards to a European norm [17].…”
Section: Social Work As a Global Professionmentioning
confidence: 99%
“…Its spread and development have been accompanied by a drive to attain professional status and a coherent international identity through the work of a number of international organisations concerned with social work practice and education, such as the International Federation of Social Workers (IFSW) and the International Association of Schools of Social Work (IASSW). An obvious manifestation of this is the continuing drive to develop a single global definition of what social work actually is [14][15][16]. The global nature of the profession is reflected in the large number of international professional and academic social work publications and, in Europe, the imperatives of various EU directives and initiatives like the Bologna Declaration have motivated social work educators and registering authorities International Journal of Population Research 3 to move towards a closer alignment of practice standards to a European norm [17].…”
Section: Social Work As a Global Professionmentioning
confidence: 99%
“…SDM is one link in a long chain of professional shifts social workers have dealt with in recent decades (Staniforth et al . ). Arguably, social work has always been the subject of self‐searching, aimed at defining and redefining its relationship with users of its services (Levin & Weiss‐Gal ).…”
Section: Discussionmentioning
confidence: 97%
“…These studies are predicated on the rationale that identifying the social worker role as an agent of change with a mandate for public policy advocacy increases the likelihood of participation in social action and related policy work. The literature suggests however that social workers are more likely to identify with their direct practice responsibilities and advancing change at the individual, rather than social level (Gillingham, 2007;O'Brien, 2010;Schneider & Netting, 1999;Staniforth, Fouche´, & O'Brien, 2011). Staniforth et al (2011), for example, asked 300 New Zealand social workers to provide a definition of social work.…”
Section: Social Action: From Mobilisation To Effecting Changementioning
confidence: 99%
“…The literature suggests however that social workers are more likely to identify with their direct practice responsibilities and advancing change at the individual, rather than social level (Gillingham, 2007;O'Brien, 2010;Schneider & Netting, 1999;Staniforth, Fouche´, & O'Brien, 2011). Staniforth et al (2011), for example, asked 300 New Zealand social workers to provide a definition of social work. Using thematic analysis the researchers found that the vast majority of social workers continued to define their profession in direct practice terms.…”
Section: Social Action: From Mobilisation To Effecting Changementioning
confidence: 99%